2016
DOI: 10.1371/journal.pone.0163584
|View full text |Cite
|
Sign up to set email alerts
|

"If You Have to Ask, You'll Never Know": Effects of Specialised Stylistic Expertise on Predictive Processing of Music

Abstract: Musical expertise entails meticulous stylistic specialisation and enculturation. Even so, research on musical training effects has focused on generalised comparisons between musicians and non-musicians, and cross-cultural work addressing specialised expertise has traded cultural specificity and sensitivity for other methodological limitations. This study aimed to experimentally dissociate the effects of specialised stylistic training and general musical expertise on the perception of melodies. Non-musicians an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 74 publications
4
63
1
Order By: Relevance
“…From a computational perspective, the former relies on reinforcement learning, which sets up computational principles for maximizing reward value, irrespective of music-structural specifics (Schultz, 2013). The latter deals with predictions concerning musical structure and has been modeled using statistical learning and predictive coding (Vuust et al, 2009; Hansen and Pearce, 2014; Vuust and Witek, 2014; Hansen et al, 2016). In predictive coding, PE is neither “positive” nor “negative” per se , but rather strong/weak on a single continuum (Friston and Stephan, 2007).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…From a computational perspective, the former relies on reinforcement learning, which sets up computational principles for maximizing reward value, irrespective of music-structural specifics (Schultz, 2013). The latter deals with predictions concerning musical structure and has been modeled using statistical learning and predictive coding (Vuust et al, 2009; Hansen and Pearce, 2014; Vuust and Witek, 2014; Hansen et al, 2016). In predictive coding, PE is neither “positive” nor “negative” per se , but rather strong/weak on a single continuum (Friston and Stephan, 2007).…”
mentioning
confidence: 99%
“…If the new sounds were better than expected [i.e., RPE], positive PE would result.” Assessing whether music is “structurally-better-than-expected” requires a clear definition of “structurally good.” In music listening, however, expectations more likely pertain to the structure of music (PE) than to its reward value (RPE) (Huron, 2006; Miranda and Ullman, 2007; Hansen and Pearce, 2014; Vuust and Witek, 2014; Hansen et al, 2016). Accordingly, Salimpoor et al's notion of valenced PE with respect to structural continuation is problematic because it conflates expectations about experienced pleasure and perceived sounds.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While the aforementioned studies tend to reflect differences measuring individual's musical training, other studies have suggested that factors outside of musical training such as familiarity with the genre or style of the musical material (Tervaniemi, 2009; Hansen et al, 2016) as well as other non-performative abilities can play a crucial role in perceptual models (Bigand and Poulin-Charronnat, 2006). Though literature is sparse regarding perceptual models that takes into account genre familiarity, there are a number of studies that aim at mid-level features, such as schematic expectations (Eerola et al, 2009), and that do take into account listener backgrounds and musical acculturation that can be integrated in the modeling process via mechanisms such as statistical learning (Krumhansl et al, 2000).…”
Section: Introductionmentioning
confidence: 99%